Roles of the peroxisome proliferator-activated receptors (PPARs) in the pathogenesis of nonalcoholic fatty liver disease (NAFLD) - Yuan-Ye Qiu; Jing Zhang; Fan-Yi Zeng; Yi Zhun Zhu (Elsevier, 2023)
Non-alcoholic fatty liver disease (NAFLD) encompasses a spectrum of disease phenotypes which start with simple steatosis and lipid accumulation in the hepatocytes - a typical histological lesions characteristic. It may progress to non-alcoholic steatohepatitis (NASH) that is characterized by hepatic inflammation and/or fibrosis and subsequent onset of NAFLD-related cirrhosis and hepatocellular carcinoma (HCC). Due to the central role of the liver in metabolism, NAFLD is regarded as a result of and contribution to the metabolic abnormalities seen in the metabolic syndrome. Peroxisome proliferator-activated receptors (PPARs) has three subtypes, which govern the expression of genes responsible for energy metabolism, cellular development, inflammation, and differentiation. The agonists of PPARα, such as fenofibrate and clofibrate, have been used as lipid-lowering drugs in clinical practice. Thiazolidinediones (TZDs) - ligands of PPARγ, such as rosiglitazone and pioglitazone, are also used in the treatment of type 2 diabetes (T2D) with insulin resistance (IR). Increasing evidence suggests that PPARβ/δ agonists have potential therapeutic effects in improving insulin sensitivity and lipid metabolism disorders. In addition, PPARs ligands have been considered as potential therapeutic drugs for hypertension, atherosclerosis (AS) or diabetic nephropathy. Their crucial biological roles dictate the significance of PPARs-targeting in medical research and drug discovery. Here, it reviews the biological activities, ligand selectivity and biological functions of the PPARs family, and discusses the relationship between PPARs and the pathogenesis of NAFLD and metabolic syndrome. This will open new possibilities for PPARs application in medicine, and provide a new idea for the treatment of fatty liver and related diseases.